The Art and Science of Results - Vitale, Joe (Ascent Audio, 2020)
What is the Missing Secret to Achieving Your Goals? In this fascinating, mind stretching, and empowering new book, bestselling author Dr. Joe Vitale, one of the stars of the hit movie The Secret, provides the surprising answers for achieving your goals faster than ever-even the biggest goals you can imagine! Let Dr. Vitale lead you on a journey to clear your mind of blocks and beliefs, and achieve the results that you deserve. Let him teach you The Art and Science of Results. Discover answers to these life-changing questions: Why has it been so difficult to get the results you want? What is the fastest way to get clear of hidden blocks to success? How do beliefs create reality and how can you change them? What are the nine "clearing" techniques for accelerating our results?